The 3-dB FBG bandwidth Characteristics - Hisham, Hisham K. (Iraqi Journal for Electrical and Electronic Engineering, 2020)
In this paper, the effect of the grating parameters (i.e. gratings length (Lg) and the induced index profile (Δn)); the temperature variation (T) and the applied strain change on the fiber Bragg Grating (FBG) 3dB-bandwidth (i.e. full width-half maximum (FWHM)) have successfully investigated numerically using MATHCAD software. Results show that for Lg < 7 mm, the FBG 3dB-bandwidth (i.e. full width-half maximum (FWHM)) value shows a good reliable and visible impact. Otherwise, there are no significant effects except for increasing the FBG reflectivity. Also, results show that the FWHM value has affected by the change of the Δn value. In contrast, results show that there is no significant effect of the temperature on the FWHM value. Also, results shown that the dependence of the Bragg wavelength (λB) upon both strain and temperature variations is lies within the range of 0.462 – 0.470 fm με-1 °C-1